Pacing Strategic Change: The Case of a New Venture - Gersick, Connie J. G. (Academy of Management Journal, 1994)
Theorists debate whether organizations are inertial or adaptable, but mounting evidence shows they are both, provoking questions about how shifts occur between inertia and change. Research shows performance crises can trigger reactive change, but proactive revolutions in organizations are poorly understood. In project groups, temporal pacing triggers proactive change. This longitudinal study of a venture capital?backed start-up company explored whether temporal pacing could regulate momentum and change in an organization's strategy, as it does in groups. Two forms of pacing were discovered, one time-based, with reorientations initiated at temporal milestones, the other event-based, with actions initiated when the right event occurred. The two pacing types fostered systematically different patterns of momentum and change.